(untitled) (Justicia &Derecho, 2019)
Our work deals with the institution of active standing in the examination of admissibility in the collective processes of consumers under the Law No. 19.496, envisioning the criteria that the courts have had to make such an examination. The study incorporates national and international jurisprudence related to collective processes. Special emphasis will be given to the active standing that the law regulates in collective processes, studying its requisites and effects. Finally, some constitutional reflections will be made regarding collective processes in general, and specifically, about the active standing of Law No. 19.496.